Respostas
respondido por:
0
Vamos calcular com o Teorema Pitagoras na seguinte formula dada :
hipotenusa^2 = cateo1^2 + cateto2^2
(8)^2 = (5)^2 + cateto2^2
64 = 25 + cateto2^2
25 + cateto2^2 = 64
cateto2^2 = 64 - 25
cateto2^2 = 39
cateto2 = \/39
cateto2 = 6,24
hipotenusa^2 = cateo1^2 + cateto2^2
(8)^2 = (5)^2 + cateto2^2
64 = 25 + cateto2^2
25 + cateto2^2 = 64
cateto2^2 = 64 - 25
cateto2^2 = 39
cateto2 = \/39
cateto2 = 6,24
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás